Accounting in e-Banks and the challenges they face: دراسة استطلاعية في عينة من المصارف التجارية في محافظة السليمانية - Aziz, Hemn M.; Faraj, Hiwa Ali; Najim, Basira Majeed (Journal of University of Human Development, 2018)
Abstract Electronic banking has developed as a result of the technological revolution the world witnessed in the last several decades. Here, banking transactions are carrying out in an electronic form with the support of the internet. Banks can provide their normal services such as cash withdrawals and transfer without the need of customers to visit their physical branches. The purposes of this paper is to (1) identify the significant of electronic banks, (2) highlight the key challenges facing electronic banks in Kurdistan Region, and (3) determine the obstacles facing accountants and auditors in processing their tasks electronically. In attempting to achieve these goals, qualitative data is collected via constructing a questionnaire survey. They were distributed to the executive directors and head of account and IT departments of seven commercial banks which have adopted electronic banking services. Using linear regression analysis, the findings of this study highlighted the weakness of the current rules and regulations of electronic banking in the Kurdistan Region. We found that electronic systems have a significantly positive influence on accounting and auditing procedures, as electronic systems need to be consistent with accounting and auditing standards. The study recommends that it is necessary for the Central Bank of Iraq to review the laws and legislation in organizing electronic banks. Additionally, training and qualifying specialists in the field of IT, communications, networking, in addition to electronic accounting and auditing are also recommended.